First Observation of the Decay B0s → K-μ+νμ and a Measurement of |Vub|=|Vcb| - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Dziewiecki, Michal; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2021)
The first observation of the suppressed semileptonic B0s→K−μ+νμ decay is reported. Using a data sample recorded in pp collisions in 2012 with the LHCb detector, corresponding to an integrated luminosity of 2 fb−1, the branching fraction B(B0s→K−μ+νμ) is measured to be [1.06±0.05(stat)±0.08(syst)]×10−4, where the first uncertainty is statistical and the second one represents the combined systematic uncertainties. The decay B0s→D−sμ+νμ, where D−s is reconstructed in the final state K+K−π−, is used as a normalization channel to minimize the experimental systematic uncertainty. Theoretical calculations on the form factors of the B0s→K− and B0s→D−s transitions are employed to determine the ratio of the Cabibbo-Kobayashi-Maskawa matrix elements |Vub|/|Vcb| at low and high B0s→K− momentum transfer.
Im Titel sind jeweils "0", "-" und "+" hochgestellt und "s", "ub" und "cb" tiefgestellt
Im Titel ist "mu" in νμ tiefgestellt
Gesehen am 15.03.2021